Comparison of interfragmentary compression across simulated condylar fractures repaired using four techniques - Brabon, Ashley; Hughes, Kristopher James; Labens, Raphael (Frontiers in Veterinary Science, 2023)
Equine condylar fractures are commonly repaired using cortex screws applied in lag fashion. Inadequate interfragmentary compression can lead to post-operative complications. Lateral condylar fractures were simulated in 21 cadaver limbs (8 third metatarsals, 13 third metacarpals). Pressure-sensitive film (Prescale®, Fuji Photo Film Co.) was placed in each osteotomy prior to repair with 4.5mm diameter cortex screws placed in lag fashion. Screws were placed in linear (L), triangular (T), linear plus a washer (LW) and sequentially tightened triangular configurations (TD1). All screws were tightened to a torque of 4 Nm. Pressure prints obtained were scanned using dedicated software (Fuji FPD-8010E, Fuji Photo Film Co.). A Bayesian Network (BN) model was developed to investigate the impact and interrelationship of each factor on interfragmentary compression. Sixty-three repairs (20*L, 24* T, 11*TD1 and 8*LW) performed on 21 limbs were included in the analysis. The BN predicted mean contact area (± s.d.) for pressures within the operating range of the prescale film (≥ 2.5 Megapascals (MPa) ≤ 10MPa) by L, T, TD1 and LW repairs were 403mm2 ± (140), 411mm2 ± (120), 403mm2 ± (120) and 366mm2 ± (70). The mean contact area (± s.d.) created by L, T, TD1 and LW repairs at pressures > 10MPa were 112 mm2 ± (48), 167mm2 ± (67), 142mm2 ± (50) and 100mm2 ± (27). When pressures ≥2.5 MPA to ≤10 MPa were considered, the construct (T or L), washer and screw tightening sequence variables had a very low effect on interfragmentary contact area. At pressures > 10MPa BN sensitivity findings were 16.3%, 5.03% and 0.133% for construct (T or L), washer and screw tightening sequence. The BN model indicated that triangular repair had a weak influence in the ≥ 2.5MPa ≤ 10MPa range and a moderate influence in the <10MPa range, on interfragmentary compression. The addition of a washer and screw tightening sequence had a weak influence on interfragmentary compression at all pressures. The results show that triangular repairs create larger interfragmentary contact areas at greater interfragmentary pressure in simulated condylar fractures, however it is unknown if this results in improved repair stability in the clinical scenario.